Relationship of self-rated health with fatal and non-fatal outcomes in cardiovascular disease: a systematic review and meta-analysis. - Nahal Mavaddat; Richard A Parker; Simon Sanderson; Jonathan Mant; Ann Louise Kinmonth (PLoS ONE, 2014)
Background People who rate their health as poor experience higher all-cause mortality. Study of disease-specific association with self-rated health might increase understanding of why this association exists. Objectives To estimate the strength of association between self-rated health and fatal and non-fatal cardiovascular disease. Methods A comprehensive search of PubMed MEDLINE, EMBASE, CINAHL, BIOSIS, PsycINFO, DARE, Cochrane Library, and Web of Science was undertaken during June 2013. Two reviewers independently searched databases and selected studies. Inclusion criteria were prospective cohort studies or cohort analyses of randomised trials with baseline measurement of self-rated health with fatal or non-fatal cardiovascular outcomes. 20 studies were pooled quantitatively in different meta-analyses. Study quality was assessed using Newcastle-Ottawa scales. Results 'Poor' relative to 'excellent' self-rated health (defined by most extreme categories in each study, most often' poor' or 'very poor' and 'excellent' or 'good') was associated over a follow-up of 2.3-23 years with cardiovascular mortality in studies: where varying degrees of adjustments had been made for cardiovascular disease risk (HR 1.79 (95% CI 1.50 to 2.14); 15 studies, I2 = 71.24%), and in studies reporting outcomes in people with pre-existing cardiovascular disease or ischaemic heart disease symptoms (HR 2.42 (95% CI 1.32 to 4.44); 3 studies; I2 = 71.83%). 'Poor' relative to 'excellent' self rated health was also associated with the combined outcome of fatal and non-fatal cardiovascular events (HR 1.90 (95% CI 1.26 to 2.87); 5 studies; I2 = 68.61%), Self-rated health was not significantly associated with non-fatal cardiovascular disease outcomes (HR 1.66 (95% CI 0.96 to 2.87); 5 studies; I2 = 83.60%). Conclusions Poor self rated health is associated with cardiovascular mortality in populations with and without prior cardiovascular disease. Those with current poor self-rated health may warrant additional input from health services to identify and address reasons for their low subjective health.